1994
DOI: 10.1002/cyto.990180304
|View full text |Cite
|
Sign up to set email alerts
|

Quality control in flow cytometry for diagnostic pathology: II. A conspectus of reference ranges for lymphocyte immunophenotyping

Abstract: Immunophenotyping, as many other clinical assays, is interpreted only in the context of reference values obtained from healthy control individuals. While the use of these reference values, or ranges, has been commonplace in the clinical flow cytometry laboratory for well over a decade, there has been little consensus in standardizing how these values should be obtained, analyzed, or expressed. This report reviews the variables to be considered in establishing reference ranges and statistical methods which can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
37
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 54 publications
10
37
2
Order By: Relevance
“…The percentage of T lymphocytes in our group of control cases (see above) ranged from 9% to 83%, which is in agreement with published data (33,34). Therefore, the predominance of a T-cell population is not diagnostic per se of malignancy.…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of T lymphocytes in our group of control cases (see above) ranged from 9% to 83%, which is in agreement with published data (33,34). Therefore, the predominance of a T-cell population is not diagnostic per se of malignancy.…”
Section: Discussionsupporting
confidence: 92%
“…coexpressed by nearly all CD19-positive B cells. 11,15 In contrast, we found that the expression of CD20 and FMC7 did not parallel that of CD19 and CD79a on splenic B cells. To exclude the possibility that the differences between the results of our study and those of previous reports are due to the use of different flow cytometry protocols, lymphocytes from normal peripheral blood and lymph nodes were analyzed using the same method and reagents as used for spleen cells.…”
Section: Discussioncontrasting
confidence: 70%
“…11 The frequency of g/d TCR-positive cells was 6% and 11% of all CD3 positive T cells in normal and reactive spleen, respectively. These values may appear much lower than those previously reported by studies which showed that g/d TCR-positive cells represent about 17% of all CD3 positive cells in the red pulp of the spleen.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations